2013
DOI: 10.1210/en.2012-2275
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Corn Zein Hydrolysate Stimulates GLP-1 and GIP Secretion and Improves Glucose Tolerance in Male Normal Rats and Goto-Kakizaki Rats

Abstract: We have previously demonstrated that ileal administration of the dietary protein hydrolysate prepared from corn zein (ZeinH) stimulated glucagon-like peptide-1 (GLP-1) secretion and attenuated hyperglycemia in rats. In this study, to examine whether oral administration of ZeinH improves glucose tolerance by stimulating GLP-1 and glucose-dependent insulinotropic polypeptide (GIP) secretion, glucose tolerance tests were performed in normal Sprague-Dawley male rats and diabetic Goto-Kakizaki (GK) male rats. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 43 publications
2
45
1
1
Order By: Relevance
“…with saline or Ex9 30 min before light offset and thereafter with intragastric water, gallic acid or GSPE 15 min before light offset. Chow intake was subsequently measured after it was reintroduced [29,30,31]. The Ex9 dose was studied previously to rule out any effect on food intake and to confirm its antagonistic effect on i.p.…”
Section: Methodsmentioning
confidence: 99%
“…with saline or Ex9 30 min before light offset and thereafter with intragastric water, gallic acid or GSPE 15 min before light offset. Chow intake was subsequently measured after it was reintroduced [29,30,31]. The Ex9 dose was studied previously to rule out any effect on food intake and to confirm its antagonistic effect on i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Pioneering research on protein hydrolysates are being performed by the research group of Hira and Hara at Hokkaido University, which reported the GLP‐1 secretion‐enhancing effect and hyperglycemia‐suppressing effect of the hydrolysate of zein, a maize‐derived protein . Furthermore, GLP‐1 secretion‐promoting effects via mitogen‐activated protein kinase by meat protein hydrolysates have been reported.…”
Section: Dietary Factors and Stimulation Of Glp‐1 Secretionmentioning
confidence: 99%
“…Another research group also reported the GLP-1 secretion-enhancing effects of casein and proteins from codfish, egg, and wheat, as well as the stimulation of GLP-1 secretion by egg protein hydrolysate [18]. Pioneering research on protein hydrolysates are being performed by the research group of Hira and Hara at Hokkaido University, which reported the GLP-1 secretion-enhancing effect and hyperglycemia-suppressing effect of the hydrolysate of zein, a maize-derived protein [19][20][21]. Furthermore, GLP-1 secretion-promoting effects via mitogen-activated protein kinase by meat protein hydrolysates [22] have been reported.…”
Section: Amino Acids Proteins and Protein Hydrolysatesmentioning
confidence: 99%
“…Silk fibroin hydrolysate exhibited antidiabetic effects in a non-insulindependent diabetes mellitus mouse model (Do et al, 2012). Oral administration of corn zein hydrolysate was proved to improve glucose tolerance in normal and diabetic rats (Higuchi et al, 2013). Peptides from the macroalga Palmaria palmata were purified and exhibited dipeptidyl peptidase IV inhibitory effects, suggesting their potential as functional food ingredients in the prevention and management of type 2 diabetes (Harnedy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%